Leveraging Cultural Wealth, Identities and Motivation: How Diverse Intersectional Groups of Low-Income Undergraduate STEM Students Persist in Collegiate STEM Environments - Raeshan D. Davis; Zakiya Wilson-Kennedy (MDPI AG, 2023)
Grounded in a conceptual framework incorporating intersectionality, motivation, self-determination, and self-efficacy, this empirical study investigated how individuals' identities, mindsets, and resources in educational environments intentionally cultivated to support their decision-making, development, and connections in the science community, can significantly increase the recruitment, persistence, and success of low-income, academically talented science students from diverse backgrounds. Several factors-academic performance in coursework, self-image, self-agency, financial support, and social integration in the science culture-continue to significantly impact student retention and persistence in STEM disciplines. Many of these factors are negatively affected based on a students' intersecting identities, which can be detrimental to their academic success if not addressed. We found that additional considerations to factor in concerning low-income students from diverse backgrounds that is pertinent to supporting their persistence and success in the postsecondary STEM educational context.